Analyzing the Economic Effects of Military Expenditures in ASEAN Countries - Ledesma, Ivan; Quetua, Samuel Marcial; Yang, Tsang-Hern; Rosete, Marie Antoinette (IJOSMAS, 2022)
There have been numerous studies conducted towards explaining the relationship of military expenditure to economic growth, investment, and unemployment, but no conclusive verdict can be made due to varying outcomes. To contribute to this field of study, the researchers are using the OLS and Cochrane-Orcutt model to determine the linear effect of military expenditure on the dependent variables. The sample countries will be classified according to their level of military spending and income group to examine a possible existence of a trend. The regression results show that the classification of countries has no bearing with regards to the impact of military spending on economic growth, investment, and unemployment, rather, the impact is dependent on the specific situation of each country. Moreover, as past studies implied a transitive attribute towards the relationship of the variables, this study produces a modified assumption that if economic growth is negative, it does not mean that investment and employment will be negative for they may be insignificant, it means that if either or both of the variables are significant, they will follow the same relationship of military expenditure and economic growth. Keywords: military expenditure, economic growth, investment, unemployment